Determination of regularities of heat resistance under flame action on wood wall with fire-retardant varnish - Tsapko, Yuriy; Lomaha, Vasyl; Tsapko Аleksii; Mazurchuk, Serhii; Horbachova, Oleksandra; Zavialov, Denys (Eastern-European Journal of Enterprise Technologies, 2020)
An analysis of fire-retardant materials for wooden building structures is carried out and the need to develop reliable methods for studying the process of ignition and flame propagation on the surface of a building structure, necessary for creating new types of fire-retardant materials, is found. Therefore, it is necessary to determine the conditions for forming a thermal conductivity barrier and find a mechanism for inhibiting heat transfer to the material. In this regard, a computational and analytical method for determining thermal conductivity when using a fire-retardant varnish as a coating is developed, which allows assessing the coefficient of thermal conductivity under high temperature action. According to experimental data and theoretical dependences, the coefficient of thermal conductivity of the fire-retardant coked foam layer of 0.36 W/(m∙K) is calculated, which, accordingly, ensures the heat resistance of wood. As a result of research, it is proved that the process of heat insulation of a wooden structure consists in the formation of soot-like products on the surface of natural combustible material. This made it possible to determine the conditions for fireproofing wood by forming a thermal conductivity barrier during the decomposition of varnish into foamed coke. Experimental studies confirmed that a sample of fireproof wood withstood the temperature effect of the heat flux for 900 s. The maximum possible temperature penetration through the coating is evaluated. It is found that under the temperature effect on the sample, which significantly exceeds the ignition temperature of wood, on the unheated surface of the sample, this value did not exceed 180 °C. Thus, there is reason to assert the possibility of directional regulation of wood fire protection processes using fire-retardant coatings that can form a protective layer on the material surface that inhibits wood burnout